2007
DOI: 10.1002/app.27482
|View full text |Cite
|
Sign up to set email alerts
|

Tensile behavior of polypropylene blended with bimodal distribution of styrene‐ethylene‐butadiene‐styrene particle size

Abstract: ABSTRACT:The objective is to characterize the effects of the bimodal distribution of rubber particles and its blend ratio on the mechanical properties of the thermoplastic polypropylene blended with two different styrene-ethylenebutadiene-styrene triblock copolymer at the intermediate and high strain rates. Tensile tests are conducted at the nominal strain rates from 3 3 10 21 to 10 2 (1/s). Phase morphology is investigated to estimate the bimodal rubber particle size distribution. In addition, the in situ obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…Crazing generally occurs when localized regions yield, forming an interconnected array of microvoids (Mae et al, 2008). Craze bands formed perpendicular to the loading axis, and failure occurred within these whitened areas where some evidence of localized fiber delamination was also observed.…”
Section: Discussionmentioning
confidence: 98%
“…Crazing generally occurs when localized regions yield, forming an interconnected array of microvoids (Mae et al, 2008). Craze bands formed perpendicular to the loading axis, and failure occurred within these whitened areas where some evidence of localized fiber delamination was also observed.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, two blends (SEBS A/ SEBS B = 5/5 and 10/10 wt %) were observed by TEM. 9) In our previous study, three blends (SEBS A/SEBS B = 7.5/22.5, 15/15 and 22.5/7.5 wt %) were observed by TEM. The obtained results showed that the two step blending procedure worked well for making the bimodal particle size distribution in the present blends.…”
Section: Morphological Investigationmentioning
confidence: 91%
“…The elliptical shape of elastomer particles was also obtained in the other elastomer blended PP produced by injection molding in the previous studies by the same author. 6,[13][14][15][16][17] The mean approximate diameter of EPR was 0.7 lm based on the image analysis. In the image analysis, the commercial based software (Azo-kun, Asahi Kasei Engineering, Japan) was used.…”
Section: Materials and Specimen Preparationmentioning
confidence: 99%